2016
DOI: 10.1186/s13058-016-0724-2
|View full text |Cite|
|
Sign up to set email alerts
|

Expression and methylation patterns partition luminal-A breast tumors into distinct prognostic subgroups

Abstract: BackgroundBreast cancer is a heterogeneous disease comprising several biologically different types, exhibiting diverse responses to treatment. In the past years, gene expression profiling has led to definition of several “intrinsic subtypes” of breast cancer (basal-like, HER2-enriched, luminal-A, luminal-B and normal-like), and microarray based predictors such as PAM50 have been developed. Despite their advantage over traditional histopathological classification, precise identification of breast cancer subtype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 78 publications
8
67
0
Order By: Relevance
“…This suggests that the luminal A samples which are closest to luminal B samples in the PCA tend to be worse tumours. This is consistent with the literature which describes luminal B cancer as a more severe disease (Dai et al (2015)), as well as Netanely et al's observation that luminal cancers exist along a phenotypic continuum of severity (Netanely et al (2016)). Thus, our method provides a biological explanation for some of the variance associated with the diagnostically-relevant differences in luminal sub-types.…”
Section: Kinetochore Organisation Associates With Tumour Severity Witsupporting
confidence: 92%
See 2 more Smart Citations
“…This suggests that the luminal A samples which are closest to luminal B samples in the PCA tend to be worse tumours. This is consistent with the literature which describes luminal B cancer as a more severe disease (Dai et al (2015)), as well as Netanely et al's observation that luminal cancers exist along a phenotypic continuum of severity (Netanely et al (2016)). Thus, our method provides a biological explanation for some of the variance associated with the diagnostically-relevant differences in luminal sub-types.…”
Section: Kinetochore Organisation Associates With Tumour Severity Witsupporting
confidence: 92%
“…After filtering any genes with zero counts across all samples, we performed an effective library size normalisation of the count data using DESeq2 (Anders and Huber (2010)). To retrieve luminal A (LumA) and luminal B (LumB) sub-type status for the TCGA BRCA samples, we downloaded the "PAM50" labels from the supplementary data of Netanely et al (2016). With 1148 PAM50 labels retrieved, we excluded patients that had more than one tumour sample sequenced.…”
Section: Data Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…After publication of this article [1], the authors requested to add an official acknowledgement for using the TCGA Breast Cancer dataset in their article. The following information has therefore been added to the Acknowledgements section: “The results published here are based upon data generated by The Cancer Genome Atlas managed by the NCI and NHGRI.…”
Section: Erratummentioning
confidence: 99%
“…An early version of PROMO was developed as part of a study where we identified distinct prognostic subgroups in Luminal-A breast tumors based on expression and methylation data [17]. The analysis workflow in that project provides an example of the key steps in a typical application of PROMO ( Figure 1): Data are imported, filtered and preprocessed.…”
Section: Introductionmentioning
confidence: 99%